The Modulation of Estrogen-Induced Apoptosis as an Interpretation of the Women’s Health Initiative Trials - Jordan, V Craig (Expert Rev Endocrinol Metab, 2015)
The Women’s Health Initiative (WHI) consisted of two placebo controlled trials: one in women with a uterus, using Conjugated Equine Estrogen (CEE) plus medroxyprogesterone acetate (MPA), and the second trial in women without a uterus used CEE alone. The study population average age was approximately 63 years. Although the predicted rise in breast cancer occurred in the MPA plus CEE trial, the CEE alone trial, had a sustained decrease in breast cancer incidence. A unifying theory is presented that explains the decrease in breast cancer based on the new biology of estrogen-induced apoptosis in long term estrogen deprived nascent breast cancer cells. Glucocorticoids block estrogen-induced apoptosis and MPA has glucocorticoid activity. This is why MPA increases breast cancer when used with CEE as menopausal hormone replacement. A safer menopausal hormone therapy can now be designed with a more selective synthetic progestin such as norethindrone acetate.